Digital Religiosity: Challenges in Strengthening the Islamic Character of Generation Alpha on Social Media - Siti Sundari; Wahyu Hidayat; Rachmat Rifky Septian; Hairiyanto Hairiyanto (UIN Fatmawati Sukarno Bengkulu, 2026)
Background: Generation Alpha (born after 2010) has grown up in an era where digital technology and social media are integrated into nearly every aspect of life, giving rise to the concept of